The Currency of Gender: Student and Institutional Responses to the First Gender Unit in an Australian Journalism Program (Journalism & mass communication educator, 2015)
This paper reports on the development and implementation of the first unit in an Australian university undergraduate journalism program to specifically examine the gendered nature of both news content and production processes. The paper outlines why such a unit is important to addressing entrenched industry bias, the core content, and student and institutional responses. It notes the initial limitations and ongoing impediments to developing similar modules in other journalism programs. While the paper laments the parlous state of critical feminist reflection in Australian journalism education, its main aim is to bear witness to the success of the ground-breaking unit and to encourage journalism educators worldwide to embrace gender (and diversity) education in their curricula.
https://katalog.adlr.link/Record/ai-68-OLC1963858387